The Impact of Single Motherhood on a Child’s Emotional Disposition in Asia: A Scoping Review - Ghani, Afiq Azri Mohd; Yob, Fatin Syamilah Che; Pek, Lim Seong; Mee, Rita Wong Mee; Ismail, Md Rosli; Tazli, Uzzairah Nabila Ahmad; Shahdan, Tengku Shahrom Tengku (UI Scholars Hub, 2023)
Corresponding to the current pandemic issue, Covid-19 has driven unprecedented economic loss and instability to many, particularly among low-income families, especially in Asia. In context, families involved single mothers who are markedly affected by job loss; thus, low-income households had markedly affected the well-being and development of children. In addition to family environment, sociodemographic variables, such as socioeconomic status, educational level of parents, and parental conflict, had also been associated with problematic or competent behaviors during childhood. This scoping review aimed to determine current knowledge regarding the impact of single motherhood on the emotional well-being of a child. This review was reported in accordance with the guidelines of the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Three databases, namely Scopus, Web of Science, and Education Resources Information Center (ERIC), were used for data scoping. A total of 341 studies were identified, but only 15 studies conducted in the Asian continent were eligible for selection. Results showed five significant findings concerning parent–child dysfunctional interaction, time spent, family socioeconomic status, parenting skills, and parental styles that impacted the emotional well-being of children, causing child development delay and delinquency.